Development of standard protocols for macroinvertebrate assessment of soft‐bottomed streams in New Zealand - John R. Maxted; Brent F. Evans; Mike R. Scarsbrook (New Zealand Journal of Marine and Freshwater Research, 2003)
Macroinvertebrate communities in hard‐bottomed (HB) and soft‐bottomed (SB) streams were compared to address questions on sample substrata, sample area, and data interpretation. Communities at HB and SB reference sites (native bush catchments) were distinctly different. SB reference sites had 50% of the total taxa, 33% of the Ephemeroptera, Plecoptera, and Trichoptera (EPT) taxa, and significantly lower Macroinvertebrate Community Index (MCI) and Semi‐Quantitative MCI (SQMCI) scores than HB reference sites. Ten EPT genera were abundant (>20 individuals per sample) at HB reference sites compared with one EPT genus ( Zephlebia ) at SB reference sites. The densities of macroinvertebrates at SB reference sites were